Recent advances in microfluidic technologies for cell-to-cell interaction studies. Issue 2 (16th November 2017) - Rothbauer, Mario; Zirath, Helene; Ertl, Peter
Abstract : Microfluidic cell cultures are ideally positioned to become the next generation of in vitro diagnostic tools for biomedical research, where key biological processes such as cell signalling and dynamic cell-to-cell interactions can be reliably analysed under reproducible physiological cell culture conditions. Abstract : Microfluidic cell cultures are ideally positioned to become the next generation of in vitro diagnostic tools for biomedical research, where key biological processes such as cell signalling and dynamic cell-to-cell interactions can be reliably analysed under reproducible physiological cell culture conditions. In the last decade, a large number of microfluidic cell analysis systems have been developed for a variety of applications including drug target optimization, drug screening and toxicological testing. More recently, advanced in vitro microfluidic cell culture systems have emerged that are capable of replicating the complex three-dimensional architectures of tissues and organs and thus represent valid biological models for investigating the mechanism and function of human tissue structures, as well as studying the onset and progression of diseases such as cancer. In this review, we present the most important developments in single-cell, 2D and 3D microfluidic cell culture systems for studying cell-to-cell interactions published over the last 6 years, with a focus on cancer research and immunotherapy, vascular models and neuroscience. In addition, the current technological development of microdevices with more advanced physiological cell microenvironments that integrate multiple organ models, namely, the so-called body-, human- and multi-organ-on-a-chip, is reviewed.